X‐Ray Irradiation of Pseudomonas aeruginosa Induces Biogenesis of Outer‐Inner Membrane Vesicles With Potential as a Vaccine Against Acute Pneumonia - Li Zhang; Zhixue Shen; Yanwei Chen; Cuicui Ma; Mi Huang; Yueyue He; Guilan Wang; Dan Huang; Bo Su; Boguang Jiang; Yingjie Luo; Wenfang Li; et al. (Journal of Extracellular Vesicles)
ABSTRACT Many bacteria produce extracellular vesicles (EVs) that play critical roles in various biological processes and hold significant potential for biomedical applications. However, the mechanisms underlying EV biogenesis remain incompletely understood. Using transmission electron microscopy, we demonstrate that X‐ray irradiation induces outward blebbing of the inner membrane in Pseudomonas aeruginosa PAO1 (P. aeruginosa PAO1), leading to the formation of outer‐inner membrane vesicles (OIMVs) through outer membrane pinching‐off. The endolysin Lys, which is negatively regulated by PrtR and positively regulated by PrtN, is essential for OIMV production. Lys translocates into the periplasmic space, where it disrupts the peptidoglycan layer, causing morphological changes from rod‐shaped to round cells and facilitating OIMV release. Furthermore, deletion of YciB, a protein crucial for inner membrane integrity, significantly increases OIMV production. In a murine model of acute pneumonia, OIMV immunisation significantly improves pulmonary bacterial clearance, reduces lung injury and enhances survival rates. Our findings reveal inner membrane blebbing as a novel mechanism of OIMV biogenesis in P. aeruginosa PAO1 under X‐ray irradiation and highlight the potential of OIMVs as promising vaccine candidates against P. aeruginosa infections.